Biomasa residual del cultivo de maíz duro y su potencial energético en el cantón Mocache, año 2014. Plan de disminución de quema de residuos agrícolas - Cervantes Molina, Ximena Paola (2015)
This research was conducted in the canton Mocache, Province of Los Rios, hard corn producers in order to assess the availability of residual biomass durum maize and its energy potential in Canton Mocache 2014, for which the characteristics of producers and process waste handling of hard corn, and the availability of residual biomass hard corn in the canton study determined and know the energy potential residual biomass in the study; for which the simple random probability sampling for which the equation Brito (2006) was used, where the sample for the survey was 66 producers of hard corn was applied as well to inquire about the availability of biomass design was applied completely random (DCA), 2 factorial arrangement (varieties) 3 (sites) with; to determine whether the corn biomass contributes to energy generating elements in elemental analysis which the percentage of moisture, ash and volatile material was performed was determined. Thus was revealed that 80.30% of corn growers perform a controlled biomass burning corn, the same as mostly practiced this work to prepare the ground for the next planting and 35.19% do to reduce cost and the way they have to burn it in several lots with 53.71% and 46.30% lizard to be the place where practice this activity is mostly the same land with 77.78%. It was also established that the canton Mocache brings with 316,342.89 t / year of residual mass; was learned that the biomass of 9.23% moisture corn; 10.35% 79.58% ash and volatile material with an energy potential of 4675.80 TJ / year.